2011
DOI: 10.1227/neu.0b013e31821bc46d
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Seizures or Epilepsy After Clipping or Coiling of Ruptured and Unruptured Cerebral Aneurysms in the Nationwide Inpatient Sample Database: 2002-2007

Abstract: In unruptured cerebral aneurysm patients, clipping is associated with a higher risk of seizures or epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…[3][4][5][6][7] However, our study offers substantial advances compared with these previous studies. First, we performed propensity score adjustment using numerous patient and hospital covariates to better match clipping and coiling patients and minimize selection bias, and we performed a sensitivity analysis to measure the effect of a possible unmeasured confounder.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[3][4][5][6][7] However, our study offers substantial advances compared with these previous studies. First, we performed propensity score adjustment using numerous patient and hospital covariates to better match clipping and coiling patients and minimize selection bias, and we performed a sensitivity analysis to measure the effect of a possible unmeasured confounder.…”
Section: Discussionmentioning
confidence: 94%
“…Previously published large patient database studies have demonstrated that patients who underwent clipping for unruptured aneurysms had worse outcomes compared with patients who underwent coiling. [3][4][5][6][7] However, these retrospective studies may have been affected by selection bias, because patients were not randomized to clipping or coiling. To address this concern of selection bias, we performed a propensity score analysis of patients treated with clipping or coiling of unruptured aneurysms between 2006 and 2011 to assess for disparities in periprocedural outcomes between these 2 treatment modalities.…”
mentioning
confidence: 99%
“…215,216 In terms of specific complications after UIA surgery, the rate of seizure after craniotomy for UIA is poorly defined. Analyses of administrative data sets have reported a very low incidence of 0.1% for status epilepticus 199 and as high as 9.2% when reporting any seizures, 217 although these studies do not account for preexisting seizures or use of anticonvulsant drugs. For example, in the ISUIA cohort, 4.4% of patients with surgically treated UIAs had a preexisting convulsive disorder.…”
Section: Surgical Clipping Outcomesmentioning
confidence: 99%
“…Further, most of the studies have been retrospective analyses of single-institution experiences, 10 demonstrating results with limited generalization given their inherent selection bias. The interpretation of other multicenter studies is equally limited given their focus on specific subgroup data 1,2,4,5,7,8 or their consideration of all morbidity as one variable. 3,15 The Nationwide Inpatient Sample (NIS) is a hospital discharge database that represents approximately 20% of all inpatient admissions to nonfederal hospitals in the US.…”
mentioning
confidence: 99%